Manhajun Muqtarahun Fî Ta'lim Al-Lugah Al-Arabiyyah Lil-Indunîsiyyîn Bi Istikhdâmi An-Nazâir Al-Mukhâdi'ah Fi Qâmus Al-Munawwir Min Harfi A Ila D Namûdzajan - Mifta Hurrahmi; Rizal Firdaus (Mauriduna: Journal of Islamic Studies, 2021)
تهدف هذه الدراسة إلى كشف وجود الكلمات الإندونيسية ذات النظائر المخادعة في "قاموس المنور" من حرف A إلى حرف D نموذجا، ومنهج مقترح لتعليم هذه الكلمات للإندونيسيين، ومن حيث لا يقع الإندونيسيين في سوء الفهم ويقودهم إلى فهم صحيح ويسهل لمعلمي اللغة العربية في تعليمها. إن هذه الدراسة تسلك على المنهج الوصفي التحليلي، وهو أسلوب من أساليب التحليل المركز على معلومات كافية ودقيقة عن ظاهرة أو موضوع محدد، أو فترات زمنية معلومة، وذلك من أجل الحصول على نتائج علمية ثم تفسيرها بطريقة موضيعية، وهو البحث المكتبي. ولتحليل البيانات استخدمت الباحثة منهج ميلز وحابيرمان (Miles dan Haberman) في البحث عن الكلمات ذات النظائر المخادعة لأنه يعتبر من التحليل الفني للبيانات النوعية، وتقوم بالشكل التفاعلي. وأثبتت الدراسة وجود الكلمات الإندونيسية ذات النظائر المخادعة في "قاموس المنور". وبلغ عدد الكلمات الإندونيسية ذات النظائر المخادعة 126 كلمة، وأيضا من منهج مقترح لتعليم تلك المفردات في تعليم اللغة العربية للإندونيسيين ووضعتها في صياغة الحوار، وعبر الصور، والألعاب اللغوية. The study aims to reveal the existence of Indonesian words with deceptive analogues in the “Al-Munawwir Dictionary” from the letter A to the letter D as a model, and a suggested approach to teach these words to Indonesians, and in terms of where the Indonesians do not fall into misunderstanding and lead them to a correct understanding and facilitate the teachers of the Arabic language in teaching them. This study is based on the descriptive analytical method, which is a method of analysis focused on sufficient and accurate information about a specific phenomenon or subject, or known time periods, in order to obtain scientific results and then interpret them in a topical way. To analyze the data, the researcher used Miles and Haberman method to search for words with deceptive isotopes, because it is considered a technical analysis of qualitative data, and it performs interactively. The number of Indonesian words with deceptive analogues reached 126 words, and also from proposed curriculum to teach those vocabulary in teaching Arabic to Indonesians and put it in the formulation of dialogue, and through pictures, and language games.